2021
DOI: 10.1108/jfra-05-2020-0130
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, ownership structure and firms’ financial performance: insights from Muscat securities market (MSM30)

Abstract: Purpose The purpose of this study is to investigate the relationship between selected board characteristics and ownership elements and the performance of firms listed in the Muscat Securities Market (MSM30). The examination focused on how the firm financial performance was affected by the board size, the number of board meetings and the ratio of the independent board of directors along to the ownership concentration types (i.e. institutional, state and concentrated individual ownership). Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
39
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 73 publications
11
39
1
5
Order By: Relevance
“…Regarding the impact of CG on the firms' performance, Asghar et al (2020) found that CG has a significantly positive effect on the firm's value and performance measures. Queiri et al (2021) found that the size of the board of directors positively impacts a firm's performance in nonfinancial services companies listed in the Muscat stock market, while the ratio of the independent board of directors and the number of board director's meetings were inversely affecting the firm performance. Zaid et al (2020) investigated the impact of CG practices on capital structure decisions for nonfinancial services companies listed in the Palestine securities market and found that board size and board independence are more positive under conditions of high level of gender diversity.…”
Section: Corporate Governance and Islamic Banksmentioning
confidence: 98%
“…Regarding the impact of CG on the firms' performance, Asghar et al (2020) found that CG has a significantly positive effect on the firm's value and performance measures. Queiri et al (2021) found that the size of the board of directors positively impacts a firm's performance in nonfinancial services companies listed in the Muscat stock market, while the ratio of the independent board of directors and the number of board director's meetings were inversely affecting the firm performance. Zaid et al (2020) investigated the impact of CG practices on capital structure decisions for nonfinancial services companies listed in the Palestine securities market and found that board size and board independence are more positive under conditions of high level of gender diversity.…”
Section: Corporate Governance and Islamic Banksmentioning
confidence: 98%
“…Financial pellucidity, containing clearness of transactions, is one of the mainstays of sustainability [75,76]. The research sphere analysing the relationships between the ownership structure, monitoring activities through the accounting information and sustainability is an important part of contemporary finance and accounting [77][78][79][80]. Earnings management influences monitoring activities of the enterprises, therefore it has a direct relationship with sustainability and economic performance [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…The control variables have been selected based on a detailed literature review. Prior scholars (Abraham and Singh, 2016;Benkraiem et al, 2017;Bova et al, 2015;Diasc et al, 2020;Mathew et al, 2016;Mathew et al, 2018;Pergola and Joseph, 2011;Petra and Dorata, 2008;Queiri et al, 2021) proved that the following control variables are the significant attributes for explaining corporate governance, executive compensation and their relation to risk: firm size, leverage, sector, institutional ownership, firm in loss, CEO's tenure, nationality, age and ownership, international board of directors (BOD), the board size, independent BOD, risk committee and CEO duality ( Because of the panel data set and the significant results of the Hausman test, fixed effect regression is the most appropriate technique for the models in this paper (Baltagi, 2012). Thus, the fixed firm-year effect regression analysis with robust standard errors was used to test the hypotheses.…”
Section: Model and Methodsmentioning
confidence: 99%
“…). For instance,Mathew et al (2018),Abraham and Singh (2016) andMathew et al (2016) found a strong association between corporate governance structures, especially for the board structure and CEO power/duality and risk Queiri et al (2021),Bova et al (2015). andPergola and Joseph (2011) have highlighted the link between institutional ownership and CEO's ownership and corporate governance structures.Table1…”
mentioning
confidence: 98%